XMMU J050722.1−684758: discovery of a new Be X-ray binary pulsar likely associated with the supernova remnant MCSNR J0507−6847. Issue 1 (18th March 2021) - Maitra, C; Haberl, F; Maggi, P; Kavanagh, P J; Vasilopoulos, G; Sasaki, M; Filipović, M D; Udalski, A
ABSTRACT: We report the discovery of a new high-mass X-ray binary pulsar, XMMU J050722.1−684758, possibly associated with the supernova remnant (SNR) MCSNR J0507−6847 in the Large Magellanic Cloud, using XMM–Newton X-ray observations. Pulsations with a periodicity of 570 s are discovered from the Be X-ray binary XMMU J050722.1−684758 confirming its nature as a HMXB pulsar. The HMXB is located near the geometric centre of the SNR MCSNR J0507−6847(0.9 arcmin from the centre) which supports the XRB-SNR association. The estimated age of the SNR is 43–63 kyr years which points to a middle aged to old SNR. The large diameter of the SNR combined with the lack of distinctive shell counterparts in optical and radio indicates that the SNR is expanding into the tenuous environment of the superbubble N103. The estimated magnetic field strength of the neutron star is B ≳ 10 14  G assuming a spin equilibrium condition which is expected from the estimated age of the parent remnant and assuming that the measured mass-accretion rate remained constant throughout.